Antecedents to Organizational Issue Interpretation: The Roles of Single-Level, Cross-Level, and Content Cues - Thomas, James B.; Shankster, Laura J.; Mathieu, John E. (Academy of Management Journal, 1994)
This study examined the relationship between individual, group, and organizational antecedent variables and strategic and political interpretations of key organizational issues. Results showed that (1) the three sources of influence were linked to strategic and political interpretations differently, and (2) issue content combined with context and interpretive outcomes to define three distinct interpretive environments. The configurational analyses that define these environments unmask the cross-level effects of several variables on managerial interpretation. We discuss implications for studying interpretation at multiple levels and future research directions.